Bosnia Today: Despair, Hope, and History. - HUNT, WILLIAM; DURAKOVIC, FERIDA; RADELJKOVIC, ZVONIMIR (Dissent (0012-3846))
The article looks at political, social, and economic conditions in Bosnia and Herzegovina, or Bosnia, as of 2013. It cites the country's 1990s war and the government established under the 1995 Dayton, Ohio, Peace Accords as critical elements in creating ongoing problems in the country, particularly ethnic conflicts. It notes that the country's constitution divided it into two entities, Federation of Bosnia and Herzegovina and Republika Srpska, with Croats and Bosnian Muslims primarily in the former and Serbs primarily in the latter. Topics include the non-ethnic "raja" self-identification and the Bosnian Social Democratic Party (SDP).